Characteristics of Crassostrea Oyster Cytochrome Oxidase Subunit I (Coi) Gene As Species Identity In Delta Cimanuk, West Java - Dian Rezki Muliani; Fredinan Yulianda; Nurlisa A Butet (Masyarakat Moluska Indonesia, 2020)
Oysters belong to the Crassostrea, which is a type of shellfish that lives as benthos in waters under the same substrate and environmental conditions will exhibit similar morphological changes in response. There are many types of oysters that have a similar shape are often an obstacle to differentiate of Crassostrea species through morphological identification. The purpose of this research was to identify the types of oysters found in the waters of Delta Cimanuk through analysis of the morphology and nucleotide diversity of Cytochrome Oxidase subunit I (COI) gene, as basic information on proper management and conservation. The morphological identification results show that there were two species of the Crassostrea. Identification of species through the Barcoding DNA technique shows that there is one type of oyster: Crassostrea iredalei with an accuracy of 99.5%.